2015
DOI: 10.1186/s13601-015-0076-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of IL‐33 and mast cells in allergy and inflammation

Abstract: Interleukin-33 (IL-33) is a member of the interleukin-1 (IL-1) cytokine family. It is preferentially and constitutively expressed in different structural cells such as epithelial cells, endothelial cells, and smooth muscle cells. During necrosis of these cells (after tissue injury or cell damage), the IL-33 that is released may be recognized by different types of immune cells, such as eosinophils, basophils and, especially, mast cells. IL-33 needs the specific receptor ST2 (membrane-bound receptor) and Interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
127
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(133 citation statements)
references
References 79 publications
2
127
0
4
Order By: Relevance
“…IL-33 is an “epithelial-derived” cytokine that promotes type 2–associated immune responses and has been strongly linked to allergy (8). Upon IL-33–mediated activation, mast cells have been shown to exhibit enhanced adhesion, survival, maturation, and production of several pro-inflammatory cytokines (9, 10). In basophils, IL-33–mediated activation has been described as promoting migration towards eotaxin and enhancing degranulation upon concurrent IgE-mediated activation (11).…”
Section: Introductionmentioning
confidence: 99%
“…IL-33 is an “epithelial-derived” cytokine that promotes type 2–associated immune responses and has been strongly linked to allergy (8). Upon IL-33–mediated activation, mast cells have been shown to exhibit enhanced adhesion, survival, maturation, and production of several pro-inflammatory cytokines (9, 10). In basophils, IL-33–mediated activation has been described as promoting migration towards eotaxin and enhancing degranulation upon concurrent IgE-mediated activation (11).…”
Section: Introductionmentioning
confidence: 99%
“…They differ in their mast cell-activating triggers, but are similar in that histamine and other inflammatory mast cell mediators are involved in their pathogenesis. Both disorders include the involvement of cytokines/mediators such as IL-4, IL10, IL-33 and B cell-activating factor (BAFF) - all of which contribute to the activation of many immune cells and the influx of leukocytes to the dermis and airways [1,2,3]. In both conditions, IgE is frequently elevated and anti-IgE therapy is highly effective.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, the crosstalk between immune and structural cells creates a chronic inflammatory environment which might be the major cause of the airway changes commonly observed in patients with severe asthma. Several studies have shown that IL-33 is expressed more abundantly in asthma patients than in healthy individuals [21][22][23]. Additionally, immunohistochemistry studies have reported elevated IL-33 expression in the bronchial epithelial cells of asthma patients versus healthy individuals [24].…”
Section: Discussionmentioning
confidence: 99%